2020
DOI: 10.1001/jamaoto.2019.3221
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Stapedectomy vs Hearing Aids in the Treatment of Otosclerosis

Abstract: IMPORTANCE Otosclerosis can be managed through surgical treatment, such as stapedectomy, or through hearing amplification with hearing aids. To our knowledge, there has been no cost-effectiveness analysis of these 2 treatment methods.OBJECTIVE To determine the cost-effectiveness of stapedectomy vs hearing aid use for the treatment of otosclerosis. DESIGN AND SETTINGIn this cost-effectiveness analysis, a decision tree was built to model the treatment choices for otosclerosis. The tree was run as a Markov model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
0
31
1
Order By: Relevance
“…In terms of mean costs per patient over 10 years, surgery was found to be roughly €2641.5 (US $2999.0) less expensive than hearing aids, which is in disagreement with the recent costeffectiveness study by Gillard et al, 11 which found that the lifetime incremental cost of surgery was US $2978.01 higher, although surgery was still found to be cost-effective. 11 This difference can be explained by the fact that surgery is actually 2.5 times more expensive in the United States than in France ($5394), whereas the cost of hearing aids ($2350) is similar. Furthermore, the substantial variation among devices 41 namely the probability of revision surgery (up to 10% per patient per year), the probability of postoperative hearing aid use (up to 12% per patient per year), surgery fees (increased 60%), or the proportion of patients choosing class I devices (up to 94%).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In terms of mean costs per patient over 10 years, surgery was found to be roughly €2641.5 (US $2999.0) less expensive than hearing aids, which is in disagreement with the recent costeffectiveness study by Gillard et al, 11 which found that the lifetime incremental cost of surgery was US $2978.01 higher, although surgery was still found to be cost-effective. 11 This difference can be explained by the fact that surgery is actually 2.5 times more expensive in the United States than in France ($5394), whereas the cost of hearing aids ($2350) is similar. Furthermore, the substantial variation among devices 41 namely the probability of revision surgery (up to 10% per patient per year), the probability of postoperative hearing aid use (up to 12% per patient per year), surgery fees (increased 60%), or the proportion of patients choosing class I devices (up to 94%).…”
Section: Discussioncontrasting
confidence: 62%
“…In a recent US study comparing the cost-effectiveness of surgery and hearing aids for otosclerosis, 11 the incremental cost-effectiveness ratio of stapedectomy was found to be $3918.43 per quality-adjusted life year (QALY). Based on the commonly used threshold of $50 000 per QALY, surgery was therefore deemed to be cost-effective compared with hearing aid use.…”
Section: Introductionmentioning
confidence: 99%
“…A serviceable hearing was not preserved in all patients: in 29% of cases, hearing aids were necessary. Other articles confirm a variable rate of hearing aid prescription (20-54%) [Faye-Lund et al, 1984;Lars Lundman et al, 1999;Gillard and Harris, 2020]. Majority of the recent studies suggest that better results can be achieved through the use of lasers, especially by "one-shot" CO 2 laser stapedotomy [Sergi et al, 2016].…”
Section: Discussionmentioning
confidence: 93%
“…Stapes surgery is a successful and widely adopted treatment strategy for otosclerosis [ 30 ]. While stapedotomy is the most used technique, many aspects remain to discuss, and individual preferences prevail on universal consensus.…”
Section: Discussionmentioning
confidence: 99%